The Effect of Branched Chain Amino Acids and L-Ornithine L-Aspartate Combination as The Late Evening Snacks on Nutritional Status and Minimal Hepatic Encephalopathy in Liver Cirrhosis - Eric Daniel Tenda; Irsan Hasan; Andri Sanityoso; Siti Setiati (The Indonesian Society for Digestive Endoscopy, 2012)
ABSTRACTBackground:Minimal hepatic encephalopathy (MHE) in liver cirrhotic patients is critical manifestation of low grade hepatic encephalopaty (HE), is caused quality of life decrease and risk of deteriorating into distinct HE. The study was conducted to asses the effect of combination of branched-chain amino acids (BCAA) and L-ornithine L-aspartate (LOLA), which was given late evening, on nutritional status and degree of HE.Method: This single-blind randomized study was conducted on liver cirrhotic outpatients in hepatology clinic of Cipto Mangunkusumo Hospital period June 2011-June 2012. The study subjects were divided into two groups, group of late evening snack (LS) and day snack (DS). Each group was supplemented with combination of milk of BCAAs and LOLA (3.7 g/serving). Evaluation based on history, physical examination, laboratory tests and critical flicker frequency (CFF) was performed one month after the intervention. Data were statistically analyzed with SPSS 15.Results: Thirty-two patients whose the inclusion criteria were divided into 16 subjects for each group, LS and DS. After one month of the intervention, the average level of prealbumin for DS group was increased statistically significant (p 0.001), but not significant for LS group (p = 0.259). The increase of average body weight,mid-arm muscle circumference (MAMC) and CFF test result in both groups. There was no improvement on subject global assessment (SGA) score after one month intervention in both groups.Conclusion: This study proved that giving combination of BCAAs and LOLA may improve the condition of MHE, however for nutritional status can not be assessed. Keywords: minimal hepatic encephalopathy, BCAAs, LOLA, prealbumin, SGA score, nutritional status